In Defense of Secrets - Dufourmantelle, Anne (Fordham University Press, 2021)
"Psychoanalyst and philosopher Anne Dufourmantelle drowned in 2017 in an attempt to rescue two children caught in the ocean. Her work lives on, though, in this provocative and necessary book. Through etymologies and case studies, personal history and incisive commentary on contemporary society, In Defense of Secrets returns us to the fundamental psychic scene of the secret. The secret, for Dufourmantelle, is not a code to be cracked or a firewall to be penetrated but a dynamic and powerful entity that permits relation and that ensures our humanity. Tracking the secret though art and literature, philosophy, psychoanalysis, and sociology, from the Inquisition to the present, Dufourmantelle's writing spirals around the question of the secret's value. In our age, when political and personal transparency seem to be prized above all--lives posted on the Internet, information leaked, whistles blown, taboos absent except with respect to the secret itself--In Defense of Secrets champions what remains hidden, private, veiled, hushed, just out of sight. The secret is on the side of nature, not science; organic growth, not technology; love's generosity, not knowledge's grasp. For Dufourmantelle, the secret is a powerful and dynamic thing: deadly if unheard or misused, perhaps, but equally the source of creativity and of ethics. An ethics of the secret, we can hear her say, means listening hard and sensitively, respecting the secret in its secret essence, unafraid of it and open to what it has to say."